A New Library for the Exact Sciences at the K. U. Leuven - Dekeyser, Raf (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
The Katholieke Universiteit Leuven (KUL) is the Dutch speaking part of the old university that was founded in 1425. In 1968 it was officially divided in two parts, and the French speaking part hence moved to new dwellings in Louvain-la-Neuve. The KUL is now with 25,000 students the largest university of Belgium.